(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present paper evaluates the performances of manufacturing industries with respect to total factor productivity. TFP changesand its components are estimated for 68 three-digit manufacturing industries for the period from 2008-09 to 2017-18 using data from Annual Survey of Industry (ASI) by employingMalmquist Productivity Index based data envelopment analysis. The study uses gross value added based single deflation method as output using 2011-12 as a base period. Capital stock and labour are used as inputs. The paper uses Perpetual Inventory Method to derive the measure of capital input series. It was found that the year 2015-16 has reported highest TFP growth mainly due to technological changes. All the study period exhibits positive trend in TFP growth.In the case of industry-wise analysis, the study also found that the TFP growth is highest in the manufacturer of magnetic and optical media followed by manufacturer of jewelry and related articles. It is evident form the result that the increase in TFP growth is due to technological changes and decrease in TFP growth is due to technical efficiency change.